Additive Manufacturing of Nerve Guidance Conduits for Regeneration of Injured Peripheral Nerves - Song, Shaochen; Wang, Xuejie; Wang, Tiejun; Yu, Qinghua; Hou, Zheyu; Zhu, Zhe; Li, Rui (Frontiers in Bioengineering and Biotechnology, 2020)
Repair of peripheral-nerve injuries (PNIs) with long defects is challenging. Therapeutics are being developed for bridging of nerve gaps and full recovery of nerve function. Nerve autografting is first-line treatment of PNIs but can result in loss of function at the donor site, neuroma formation, and prolonged operative time. Nerve guidance conduits (NGCs) can provide a confined space for regenerated axons and create a high-concentration microenvironment for nerve growth factors. Additive manufacturing of NGCs can offer opportunities for peripheral-nerve regeneration via production of anatomically accurate geometries, spatial distributions of cellular components, and incorporation of therapeutic biomolecules. This review examines recent advances in additive manufacture of NGCs for PNIs as well as insight into how these approaches could be improved in future studies.